A Framework for Representation and Visualization of 3D Shape Variability of Organs in an Interactive Anatomical Atlas - Heinz Handels; Hacker, Silke (Methods of information in medicine, 2009)
OBJECTIVES: Computerized anatomical 3D atlases allow interactive exploration of the human anatomy and make it easy for the user to comprehend complex 3D structures and spatial interrelationships among organs. Besides the anatomy of one reference body inter-individual shape variations of organs in a population are of interest as well. In this paper, a new framework for representation and visualization of 3D shape variability of anatomical objects within an interactive 3D atlas is presented. METHODS: In the VOXEL-MAN atlases realistic 3D visualizations of organs in high quality are generated for educational purposes using volume-based object representations. We extended the volume-based representation of organs to enable the 3D visualization of organs' shape variability in the atlas. Therefore, the volume-based representation of the inner organs in the atlas is combined with a medial representation of organs of a population creating a compact description of shape variability. RESULTS: With the framework developed different shape variations of an organ can be visualized within the context of a volume-based anatomical model. Using shape models of the kidney and the breathing lung as examples we demonstrate new possibilities such an approach offers for medical education. Furthermore, attributes like gender, age or pathology as well as shape attributes are assigned to each shape variant which can be used for selecting specific organs of the population. CONCLUSIONS: The inclusion of anatomical variability in a 3D interactive atlas presents considerable challenges, since such a system offers the chance to explore how anatomical structures vary in large populations, across age, gender and races, and in different disease states. The framework presented is a basis for the development of specialized variability atlases that focus e.g. on specific regions of the human body, groups of organs or specific topics of interest.
Keywords: Atlases as Topic; Humans; Image Processing, Computer-Assisted; Imaging, Three-Dimensional; Models, Anatomic; User-Computer Interface